2023
DOI: 10.1002/ajmg.a.63243
|View full text |Cite
|
Sign up to set email alerts
|

Global health measures from a National Down Syndrome Registry

Abstract: People with Down syndrome (DS) have a unique medical profile which may impact views of health. We aimed to study the use of global health measures for DS in a national cohort. We prospectively surveyed parents of individuals with DS from the DS-Connect ® registry with validated Patient Reported Outcomes Measurement Information System (PROMIS) ® instruments of global health. Analyses included use of scoring manuals and the PROMIS ® scoring service, descriptive statistics, and ttests. We received completed surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Prior studies have shown that many items influence QoL in individuals with DS including obesity, autism, and friendships (Haddad et al, 2018; Katsiana et al, 2020; Santoro et al, 2023; Xanthopoulos et al, 2017). A prior Australian study showed QoL in individual with DS age 16–31 years was lower with an increasing burden of medical diagnoses (Haddad et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that many items influence QoL in individuals with DS including obesity, autism, and friendships (Haddad et al, 2018; Katsiana et al, 2020; Santoro et al, 2023; Xanthopoulos et al, 2017). A prior Australian study showed QoL in individual with DS age 16–31 years was lower with an increasing burden of medical diagnoses (Haddad et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO, physical activity is any skeletal muscle movement that requires energy expenditure and can be performed at varying intensities, whereas physical fitness is a set of attributes achieved or possessed regarding the ability to perform physical activity or exercise with certain skills that affect sports achievements, such as the ability to carry out daily activities and the learning process at school [34,35,36,37,38]. Down syndrome people have been linked to a lack of physical exercise [39], and this can have an impact on poor health conditions [40]. Inadequate physical activity is defined as failing to reach recommended levels of physical activity in children and adolescents aged 5 to 17 years (60 minutes of moderate to high-intensity physical exercise daily) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Seven are examining intervention strategies for obstructive sleep apnea, three are addressing aging and AD risk, one is evaluating immune modulatory treatments for autoimmune skin A list of studies that are currently recruiting through the registry can be found on the DS-Connect website. Among the projects supported by the registry are a survey of dietary supplement use in children with DS (Lewanda et al, 2018), a survey of parents utilizing a validated tool to assess measures of global health in their children with DS (S. L. Santoro, Haugen, et al, 2023), application of the Research Attitudes Questionnaire to over 1000 families in the DS-Connect Registry (Lott et al, 2022), the comfort of caregivers with the transition to adult care for their children with DS (VanZant & McCormick, 2021), and a survey of preventive and gynecologic health care uptake by adult women with DS (Smith et al, 2020). One of the most significant events sponsored by the…”
Section: Ds Clinical Trialsmentioning
confidence: 99%